PENGARUH PERSEPSI KEMUDAHAN MENGGUNAKAN E-WALLET DAN PERSEPSI MANFAAT SERTA PROMOSI TERHADAP MINAT BELI ULANG SALDO E-WALLET OVO - Silaen, Elsa; Prabawani, Bulan (Jurnal Ilmu Administrasi Bisnis, 2019)
E-wallet is one type of electronic payment. In Indonesia, there are many e-wallet products, which are issued by banks and private sectors. PT. Visionet Internasional is one of the largest payment gateway companies in Indonesia, which have an e-walled product, called OVO. It was approved by Bank Indonesia on August 7, 2017. This study aims to determine the effect of perceived ease of use, perceived usefullness and promotion on repurchase interest of OVO balance. This is explanatory research and the sampling uses nonprobability sampling techniques, that is purposive sampling method. Data collection used questionnaires from google form. The sample used was 100 respondents using electronic wallet OVO in the city of Semarang. This study uses quantitative and qualitative analysis with validity, reliability, correlation coefficients, coefficient of determination, simple and multiple regression, significance of t test and F test. The results of multiple linear regression analysis show that there was an effect of perceived ease, perceived benefit and promotion of repurchase interest. The variable correlation coefficient of perceived ease of use, perceived usefullness and promotion for electronic wallet OVO has a strong relationship.. The determination coefficient of perceived ease of use variable on repurchase interest of OVO balance variable is 51,8%, The determination coefficient of the perceived usefullness variable on repurchase interest of OVO balance was 54,1%, and The determination coefficient of the promotion variable on repurchase interest of OVO balance was 55,9%.